Ethics and Religion: An Empirical Test of a Multidimensional Model - Parboteeah, K. Praveen (Journal of business ethics, 2008)
Although it seems that ethics and religion should be related, past research suggests mixed conclusions on the relationship. We argue that such mixed results are mostly due to methodological and conceptual limitations. We develop hypotheses linking Cornwall et al.’s (1986, Review of Religious Research, 27(3): 266–244) religious components to individuals’ willingness to justify ethically suspect behaviors. Using data on 63,087 individuals from 44 countries, we find support for three hypotheses: the cognitive, one affective, and the behavioral component of religion are negatively related to ethics. Surprisingly, one aspect of the cognitive component (i.e., belief in religion) shows no relationship. Implications for research and practice are discussed.